Monofocal hepatocellular carcinoma: How much does size matter?. (23rd November 2020) - Pelizzaro, Filippo; Penzo, Barbara; Peserico, Giulia; Imondi, Angela; Sartori, Anna; Vitale, Alessandro; Cillo, Umberto; Giannini, Edoardo G.; Forgione, Antonella; Ludovico Rapaccini, Gian; Di Marco, Maria; Caturelli, Eugenio; et al.
Abstract: Background & Aims: According to the Barcelona Clinic Liver Cancer (BCLC) staging system, monofocal hepatocellular carcinoma (HCC) is classified as early (BCLC A) irrespective of its size, even though controversies still exist regarding staging and treatment of large tumours. We aimed at evaluating the appropriate staging and treatment for large (>5 cm) monofocal (HCC). Methods: From the Italian Liver Cancer database, we selected 924 patients with small early monofocal HCC (2‐5 cm; SEM‐HCC), 163 patients with larger tumours (>5 cm; LEM‐HCC) and 1048 intermediate stage patients (BCLC B). Results: LEM‐HCC patients had a worse overall survival (OS) than SEM‐HCC (31.0 vs 49.0 months; P < .0001), and this was confirmed at multivariate analysis (HR 1.63, 95% CI 1.29‐2.05; P < .0001). The small difference in OS between LEM‐HCC and BCLC B patients (31.0 vs 27.0 months; P = .03) disappeared in the multivariate model (HR 0.98, 95% CI 0.77‐1.25; P = .89). In all monofocal tumours, treatment was the strongest independent predictor of survival, with a progressively decreasing survival benefit moving from "curative" to "palliative" therapies. The survival of resected patients with LEM‐HCC was significantly shorter than that of SEM‐HCC (44.0 vs 78.0 months; P = .002), but liver resection provided the highest survival benefit in both groups compared to other treatments. Conclusions: Monofocal HCC larger than 5 cm should not be staged as BCLC A and either a different staging system or a different subgrouping of patients (e.g. BCLC AB) should be used. Liver resection, if feasible, remains the recommended treatment for all these patients.